Computation of brush short-circuit coefficients of DC machines for extremely low speed drives - 张琪 谢国栋 黄苏融 (Journal of Shanghai University, 2006)
Short circuit due to the brushes over the commutator segments of DC machines causes reduction in the armature resistance and flux linkage, which is especially meaningful when the electric machine is running at zero or extremely low speed. In design computation of DC machines, usually the average values of the coefficients are used in consideration of the effects of the short circuit. How-ever, the average values have complicated relationships with the parameters of electric machines, therefore, no usable mathematical model has been established yet for precise computation. In this paper, a relatively simple and generalized method for precise computation of the average values of the short-circuit coefficients is proposed. This method decouples some of the machine parameters and, therefore establishes a highly parameterized mathematical model and is convenient in formulation for computation. In addition, the computation data for one and two brush pairs, which are the most common cases, is provided.